Experimental and theoretical study on longitudinal shear behavior of steel-concrete composite beams. (August 2020) - Zhang, Jing; Hu, Xiamin; Fu, Weijie; Du, Hao; Sun, Qimeng; Zhang, Qi
Abstract: Various studies have been performed on the flexural behavior of steel-concrete composite (SCC) beams. The results showed that composite beams have excellent mechanical performance. However, the research on longitudinal shear behavior of composite beams is still few. This paper focuses on an experimental study of the longitudinal shear behavior of SCC beams, including eight SCC beam specimens and six push-out specimens. The investigated parameters were the transverse reinforcement ratio, shear connection degree, longitudinal single-row and double-row studs and stud diameter. The failure modes, concrete slab strains, steel beam strains, load-deflection and load-slip curves were investigated. In addition, the effect of the test parameters on composite beams was also compared and analyzed. Based on the experimental results and open literature, a formula for calculating the longitudinal shear resistance of SCC beams with longitudinal double-row studs was proposed. Highlights: Experiments were performed on eight composite beams and six push-out specimens. Influence of the parameters on longitudinal shear behavior of composite beams were discussed. Bending tests show that transverse reinforcement ratio has great influence on failure modes of SCC beams. A model for ultimate shear resistance and flexural capacity of beams is proposed and validated.